2020
DOI: 10.1094/phyto-09-19-0348-r
|View full text |Cite
|
Sign up to set email alerts
|

Four Consistent Loci Confer Adult Plant Resistance to Leaf Rust in the Durum Wheat Lines Heller#1 and Dunkler

Abstract: The durum wheat lines Heller#1 and Dunkler from the International Maize and Wheat Improvement Center Global Wheat Program showed moderate and stable adult plant resistance to leaf rust under high disease pressure over field environments in northwestern Mexico. Leaf rust phenotyping was performed on two recombinant inbred line (RIL) populations derived from crosses of Heller#1 and Dunkler with the susceptible parent Atred#2, conducted under artificially induced Puccinia triticina epidemics in 2013, 2014, 2015, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Two durum wheat lines 'Heller#1 and 'Dunkler' from CIMMYT exhibited moderate and stable APR to leaf rust in the field. Multiple QTLs were detected on chromosomes 1BL (Lr46), 5BL (QLr.cim-5BL) and 6BL (QLr.cim-6BL) from these resistant lines [102]. The AS gene Lr18 was transferred from T. timopheevii to hexaploidy wheat chromosome 5BL [103].…”
Section: Lr/qlr On Chromosome 5bmentioning
confidence: 99%
“…Two durum wheat lines 'Heller#1 and 'Dunkler' from CIMMYT exhibited moderate and stable APR to leaf rust in the field. Multiple QTLs were detected on chromosomes 1BL (Lr46), 5BL (QLr.cim-5BL) and 6BL (QLr.cim-6BL) from these resistant lines [102]. The AS gene Lr18 was transferred from T. timopheevii to hexaploidy wheat chromosome 5BL [103].…”
Section: Lr/qlr On Chromosome 5bmentioning
confidence: 99%
“…Wang et al [30] and Muellner et al [63] identified two QTLs associated with dwarf bunt resistance, while Jiang et al [31] discovered the QFhb-5A marker for Fusarium head blight resistance. Additionally, Li et al [32] and Liu et al [33] identified markers associated with leaf rust resistance and stripe rust resistance, respectively. Other studies investigated traits such as grain yield-related traits, green bug resistance, pre-harvest sprouting resistance, kernel weight, wheat curl mite resistance, heat tolerance, and drought tolerance [34][35][36][37][38][39][40].…”
Section: Kasp Markers In Plant Breedingmentioning
confidence: 99%
“…Other studies focused on drought and low nitrogen tolerances, bacterial leaf streak resistance, cold tolerance, grain yield and yield components, salt tolerance, brown planthopper resistance, and panicle disease resistance [32,[44][45][46][47][48][49].…”
Section: Kasp Markers In Plant Breedingmentioning
confidence: 99%
“…Two durum wheat lines "Heller#1" and "Dunkler" from CIMMYT exerted moderate and stable APR to leaf rust in the field. Multiple QTLs were detected on chromosomes 1BL (Lr46), 5BL (QLr.cim-5BL) and 6BL (QLr.cim-6BL) from these resistant lines [102]. The AS gene Lr18 was transferred from Triticum timopheevii to chromosome 5BL [103].…”
Section: Lr/qlr On Chromosome 5bmentioning
confidence: 99%